Restock and straightening system for retail automation using compliant and mobile manipulation. (16th February 2020) - Garcia Ricardez, G. A.; Okada, S.; Koganti, N.; Yasuda, A.; Uriguen Eljuri, P. M.; Sano, T.; Yang, P.-C.; El Hafi, L.; Yamamoto, M.; Takamatsu, J.; Ogasawara, T.
Abstract : As the retail industry keeps expanding and shortage of workers increasing, there is a need for autonomous manipulation of products to support retail operations. The increasing amount of products and customers in establishments such as convenience stores requires the automation of restocking, disposing and straightening of products. The manipulation of products needs to be time-efficient, avoid damaging products and beautify the display of products. In this paper, we propose a robotic system to restock shelves, dispose expired products, and straighten products in retail environments. The proposed mobile manipulator features a custom-made end effector with compact and compliant design to safely and effectively manipulate products in retail stores. Through experiments in a convenience store scenario, we verify the effectiveness of our system to restock, dispose and rearrange items. GRAPHICAL ABSTRACT: